Stability and Applications of Coordination Compounds - Nanda Srivastva, Abhay (IntechOpen, 2020)
In the current era of incessant developing needs for the betterment and ease in living style for humans, technology is seeking upgraded, well structured materials for utilization in various fields of human-wellness such as medication, energy, environment protection and cleaning, food security etc. In the same direction, chemists are doing very well at synthesizing compounds and materials from different groups of chemicals. Among them, coordination compounds also play a key role in serving humanity as these compounds have a wide range of applications in health care from antimicrobial to anticancer, bioengineering, bio-mimetic models, catalysis, photosensitized materials etc. Along with development of stable coordination compounds, their extensive structural studies are also in the main line of work for researchers. Twenty-nine authors from different countries have contributed their scientific views and work in magnifying the importance and scope of coordination compounds in the present book entitled "Stability and Applications of Coordination Compounds". I hope that the book will achieve its target of supplementing the community of researchers and readers working in the field of coordination chemistry.